Religious Doubts and Emotions Toward God in Adolescents: Relation to Self-Esteem and Meaning in Life - Alice Kosarkova (Religions)
Religious doubt (RD) and emotions toward God (EtGs) are areas of religiosity and spirituality that can play a role in the development and well-being of youth. The aim of this study is to investigate whether RD and EtGs are related to self-esteem and meaning in life in adolescents and what factors may be associated with them in a secular setting. A sample of Czech adolescents (n = 984, mean age 16.61, SD 1.21; 28% male) participated in the online survey. We measured RD, EtGs, meaning in life (ML) divided into presence (ML-P) and seeking (ML-S), adolescents’ self-esteem (ASE), faith in the adolescent environment, the perception of religion and church, and religious education (RE). RD and negative EtGs were associated with reduced ML-P. Negative EtGs were associated with a reduction in ASE. However, positive EtGs were associated with an increase in ML-P. Respondents experiencing faith in their environment, having a positive view of church and religion, and enriching RE were more likely to report a decrease in RD and an increase in positive EtGs and vice versa. Our findings suggest that RD and EtGs are related to adolescents’ well-being and point to factors to be adequately addressed to minimize the negative impact of RD and promote positive EtGs.